Implementasi Sistem Informasi Manajemen Aset Inventaris Alat Kerja Karyawan Pustekinfo DPR RI Berbasis Web - David Agustianto Rapel; Zulhipni Reno Saputra; Lucky Indra Kusuma (Infotek: Jurnal Informatika dan Teknologi, 2026)
Pustekinfo DPR RI plays an important role in supporting information technology operational activities, including the management of employees’ work equipment inventory assets. Asset management that is still carried out using conventional methods has the potential to cause various problems, such as disorganized data, difficulties in monitoring asset transactions, and suboptimal supervision of asset usage. This study aims to design and implement a web-based Information System for Managing Employees’ Work Equipment Inventory Assets at Pustekinfo DPR RI in order to improve the effectiveness of asset management. The system development method used is the Waterfall method, which consists of the stages of requirements analysis, system design, implementation, testing, and maintenance. Data collection techniques include observation, interviews, and literature study. The results indicate that the developed information system is able to support structured asset management, where the Admin can manage users, asset transactions, and monitor employee data, while Users (employees) are able to manage their personal profiles independently. The results of black box testing confirm that all main system functionalities operate properly in accordance with the specified requirements, with no significant functional errors identified. Therefore, the system is considered feasible for implementation and is expected to improve efficiency, accuracy, and transparency in managing work equipment inventory assets within the Pustekinfo DPR RI environment.